Internet Network Analysis with Hierarchy Token Bucket Method at Dhyana Pura University - Trywanto Rina; Kadek Yota Ernanda Aryanto; I Made Gede Sunarya (LPPM Universitas Bina Sarana Informatika, 2023)
Bandwidth management is indispensable in computer networks. Not only to manage the needs of each individual, but also to keep the data traffic running smoothly. Dhyana Pura University is a private university that utilizes information technology in achieving optimal performance. Observation results with throughput, delay, packet loss and jitter parameters show that bandwidth management has not been done properly. Implementation of bandwidth management is done on Mikrotik Cloud Core Router and PC Router based on Ubuntu server version 16.04. One way to reduce performance degradation is to manage bandwidth. Good bandwidth management is expected to provide the right Quality of Service (QoS) for each internet service. The Hierarchy Token Bucket (HTB) method as a queuing method that regulates bandwidth usage to be given to each internet user shows more optimal results and is easier to use according to the desired needs. This is because the bandwidth is divided evenly and prevents one user from spending excessive bandwidth, so that it can increase employee satisfaction in using internet services. The results of the analysis of measuring the level of employee satisfaction with the Customer Satisfaction Index (CSI) method show that the HTB method has a total satisfaction index of 66.154% in the very satisfied category, while for troughput variables of 65.32%, delay of 67.14%, packet loss of 66.50% and jitter of 65.40%. Thus the implementation on the internet network at Dhyana Pura University using the Hierarchy Token Bucket (HTB) method is feasible to implement with a satisfied predicate.